The Interpretation of Gravity Measurements Based on Local and Regional Map Contours - Miftakhul Maulidina (Institute of Computer Science (IOCS), 2022)
The gravity method can be used to determine subsurface structures in an area. The data is data longitude, latitude, and CBA in mgal. Data processing begins with a 2D and 3D contour using the software Surfer 9. In making this contour, the coordinates in UTM coordinates. The results of two-dimensional contours, which have been obtained, then we make separation of local and regional anomalies using MagPick software. After that, both of them reprocessed using the software Surfer 9 to be